Sistem Pencatatan Perawatan Pesawat Latih di Approved Maintenance Organization Berbasis Digital - Biaggi Rayhan Pahlevie Moksen; Lilies Esthi Riyanti; Andri Kurniawan; Zulham Hidayat (Politeknik Penerbangan Indonesia Curug, 2022)
The process of aircraft production and maintenance cannot be separated from various obstacles related to data collection and documentation. So far, at AMO PPI Curug, the recording is still in hardcopy and softcopy. The hardcopy recording uses a recording form which is monthly recapitulated while softcopy recording uses Microsoft excel which is daily recapitulated from the summary of monthly data. The problem analysis found that there are frequent occurrences of input and data collection errors in the addition of flight hours that made it inefficient in work performance and schedule inspection. The research purpose is to develop an application design for a digital-based maintenance recording system on training aircraft at the Approved Maintenance Organization. The Research and development (R&D) research method are used to develop products into the results of product effectiveness testing. The research result shows that the application has web-based specifications and it can be used on a computer device platform or Smartphone gadget. The conclusion is that the electronic-based maintenance recording application can run well and it has a very good level of satisfaction in testing.